Bridging Digital Readiness in MSMEs: The Mediating Effect of Internet Motivation Between Training and Capacity Building - Lisnatiawati Saragih; Rona Tumiur Mauli Carolin Simorangkir; Djamarel Hermanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Accelerating digital transformation among Micro, Small, and Medium Enterprises (MSMEs) is crucial for enhancing competitiveness and resilience in Indonesia’s rapidly growing digital economy. This study investigates how internet learning and digital capacity building influence MSMEs’ digital readiness, with internet motivation positioned as the key mediating variable. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from MSMEs. The findings show that internet learning and digital capacity development significantly improve MSME digital readiness and internet motivation, with internet motivation emerging as the most dominant predictor. Internet motivation also plays an important mediating role in strengthening the relationship between internet learning, digital capacity development, and MSME digital readiness. These results underscore the importance of integrating structural capacity, behavioral engagement, and psychological readiness to foster meaningful digital adoption among MSMEs. This study advances the Technology Acceptance Model by combining antecedents related to motivation and capability, offering theoretical and practical insights for policymakers, digital literacy trainers, and community-based development programs.